(untitled) (Advancements in Homeopathic Research, 2025)
Background: Metabolic syndrome is a group of conditions that occurs together predisposing one to develop diabetes mellitus and cardiovascular complications. The major features of the Metabolic Syndrome are central obesity, hyperglycaemia, hypertriglyceridemia, low levels of high HDL-C and hypertension. Studies related to the efficacy of homoeopathy in Metabolic Syndrome are limited. Objective: To study the utility of homoeopathic medicines in Metabolic Syndrome Methods: A prospective clinical study was conducted at the outpatient department of Government Homeopathic Medical College, Kozhikode, using a one-group before-and-after design. The assessment was based on the change in total score before and after treatment, and the statistical test used was a paired t-test. Results: Among the subjects with Metabolic syndrome, both sexes showed equal preponderance. The highest prevalence of Metabolic syndrome was noted in the age group 50- 60 years. A majority of patients had a family history of diabetes mellitus and cardiovascular disease, indicating the possibility of hereditary influence. The study showed a significant difference in the total scores of assessment parameters before and after treatment of Metabolic syndrome with homoeopathic medicines. Additionally, more than 50% of subjects with metabolic syndrome had non alcoholic fatty liver disease (NAFLD), supporting the idea that NAFLD is the hepatic manifestation of Metabolic syndrome. Conclusion: Based on this study, homoeopathic medicines were found to be useful in managing Metabolic syndrome.